Impact Of Destination Management Organization On The Development Of Sugihen Tourism Village - Harefa, Mega Hernawati; Yogi Putra; Beby Asdilvira; Furqan (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the impact of Destination Management Organization (DMO) on the development of Sugihen Tourism Village, by examining how coordination and strategies implemented by DMO can improve economic growth, cultural preservation, and environmental sustainability in the tourism village. The study used a mixed methods approach, which integrates quantitative and qualitative methods. Quantitative data were obtained through a survey of 120 respondents, which were analyzed using multiple linear regression tests and descriptive analysis to measure the relationship between the perception of the role of DMO (independent variable) and the level of tourism village development (dependent variable). The results showed that an effective DMO role is key to optimizing tourism village development. Solid coordination, integrated marketing strategies, and active community participation are important elements that support improving the quality and competitiveness of tourism villages, while maintaining cultural and environmental sustainability. These findings are also supported by qualitative data that reveal the role of DMO in strengthening coordination between stakeholders and increasing active community participation in strategic decision making. Thus, this study confirms that the implementation of an effective, participatory, and integrated destination management model is the main key to achieving sustainable tourism village development and improving the welfare of local communities.